Experience of inclusive education in Hungary. - Г. Рего; Ю. Тордік (Borys Grinchenko Kyiv Metropolitan University, 2023)
In comparison with the trends of the previous decades, the educational process in state educational institutions has witnessed a significant increase in the number of children with special educational needs and features of psychophysical development. The military situation in Ukraine has made the issue of inclusive education more urgent. In Hungary, the emergence of two laws in the 1990s, namely Law LXXIX "On Education" of 1993, and Law XXVI "On the Rights of Persons with Disabilities and Ensuring Their Equal Opportunities" of 1998, opened new possibilities and posed new challenges to the teaching profession. Consequently, when making decisions and taking measures related to children, educators are required to treat them equally. The demand for equal treatment of all children enhances the quality of life for individuals with disabilities, enabling them to become active members of society, just like their healthy peers. Our research is not representative, and the obtained results are indicative. The purpose of the research was primarily to gain an understanding of the state of inclusive education in Hungary and lay the foundations for a more comprehensive research to borrow experience. Tasks. Based on interviews with researchers who work in the field of inclusive education in preschools and practicing educators and heads of preschool institutions with inclusive groups, we tried to cover the experience of working with children with special educational needs and their parents in Hungarian preschools. Brief Description of Research Results. Social circumstances that are constantly evolving prompt all members of the educational process, particularly educators in preschool institutions, towards adaptability, resilience, self-reflection, the renewal of educational practices and approaches, partnership among all members, and the utilization of new methods and tools. The research indicated that, from both a social and economic perspective, "investing in early childhood is a 'return on investment' in the literal sense of the word," significantly impacting their future beyond school preparedness. However, while adapting to the changing demands of society, it is crucial for preschool institutions to maintain their child-oriented focus and traditional pedagogical practices. Conclusions. In terms of the obtained results, it can be stated that for inclusive education to work successfully and yield desired results, awareness, collaboration, and receptiveness of all members of the educational process - parents, children, and educators - are essential.